Green materials and advanced manufacturing technology : concepts and applications - Chelladurai, Samson Jerold Samuel (Boca Raton, FL : CRC Press, 2021)
"This book includes recent theoretical and practical advancements in Green Composite Materials and Advanced Manufacturing Technology. It provides important original and theoretical experimental results which use non-routine technologies often unfamiliar to some readers and covers novel applications of more familiar experimental techniques and analyses of composite problems. This book gives insight and a better understanding into the development of green composite materials and advanced manufacturing technology used in various manufacturing sectors. It highlights recent trends in the fields of green composites, metal matrix composites, ceramic matrix composites, surface modification using laser cladding, types of dust collectors in waste management and recycling in industries, machinability studies of metals and composites using surface grinding, drilling, electrical discharge machining, joining of metals using friction stir welding, shielded metal arc welding and linear friction welding. This book is written for engineering students, postgraduate students, research scholars, faculty members and industry professionals those who are involved with green composite materials and advanced manufacturing technology"--
Parametric optimization of surface roughness and surface temperature during Minimum Quantity Lubrication (MQL) and conventional flood lubrication techniques in surface grinding of mild steel : A performance comparison and analysis / Gursharan Singh, Jujhar Singh, Shubham Sharma, Amoljit Singh Gill, Munish Mehta and Suresh Mayilswamy -- Importance of dust collectors in waste management and recycling in industries / S. Venkatesh, S. P. Sivapirakasam and M. Sakthiv -- Influence of nickel-based cladding on the hardness and wear behavior of hard-faced mild steel using E-7014 electrode using shielded metal arc welding / Gursharan Singh, Shubham Sharma, Jujhar Singh, Vivek Aggarwal, Amit Bansal and Suresh Mayilswamy.
OCLC-licensed vendor bibliographic record.
Keywords: Manufacturing processes; Materials; Green products; SCIENCE / Mechanics / General; TECHNOLOGY / Engineering / Chemical & Biochemical; TECHNOLOGY / Manufacturing